Evaluation Of The Parking Prohibition Policy On Roadside In Makassar City (Case Study : DR. Sam Ratulangi Street, Mariso District) - Fiqri Fezriyandi; Novayanti Sopia Rukmana (Jurnal Aktor, 2022)
This research aims to knowing the evaluation of the parking prohibition policy on the roadside in the city of Makassar (Case Study on DR. Sam Ratulangi Street, Mariso District). This research uses a Descriptive Qualitative approach. Data collection is done by technical Interview, Observation, and Documentation. The data analysis techniques used are Data Reduction, Data Presentation, Data Verification, and Drawing Conclusions. The results showed that the evaluation of the parking prohibition policy on the roadside ini Makassar City Study on the way DR. Sam Ratulangi Street, Mariso District it has been implemented but is not yet fully optimal because there are still several indicators that have not worked in accordance with William Dunn theory of public policy evaluation. In this research, the researcher examines using the theory of William Dunn (1999) and there are six indicators, namely effectiveness, efficiency, adequacy, alignment, responsiveness, and accuracy. Based on the six indicators, there are three indicators that are not good, such as adequacy, responsiveness, and accuracy, as well as three other indicators that have been running well, such as effectiveness, efficiency, and alignment.